“Para donde quiera que fuese, será buena presa”: uma análise da atuação e das relações dos corsários insurgentes de Buenos Aires, no início do século XIX - Sartoretto, Eduardo (2022)
The present dissertation aims to analyze the employment and performance of privateers groups that operated under the aegis of the insurgent government of Buenos Aires, during the first decades of the 19th century. Approaching the theme from a social perspective of History, the work seeks to contemplate the relationships established between these groups and the others involved in the independence process of the analyzed period. For that, it uses a variety of documentation that included epistolary sources, periodicals, government papers, vessel records, port records, and travelers' reports. During the construction process of this research, for a broader analysis of the object studied, we sought to explore points deemed essential for the understanding of these social and political ties, such as the organization of the privateers groups, their lifestyle, connections to and from the power and interactions with the societies that lived, circulated or, in some way, maintained links with the Rio de la Plata Region. Within the scope of the History of America and the political processes of creation of the Modern States, the study developed here, together with the base bibliography, made it possible to understand the importance of the role played by the privateers, beyond to their strategic use as a complementary military force. Through our analyses, it was possible to understand the privateering activity as a common practice, a business model created by the climate of political and social instability existing from the turn of the 18th to the 19th century; in the same way, the ship was perceived as a shelter and the privateer as a human being of his time, with personal bonds common to all human beings and whose quest for survival directed him to life at sea and to the opportunities it offered.